Mazahir al-naqdil-arabic wa fununuhu (2015)
Criticism; a Greek word derived from "krites" which denotes "judge". The judgement occurred in the process of poetic creation, which a poet might have made certain judgement about the themes and techniques to he used before presentation to the audience who will in-turn search for certain ingredients in the production. This field is a continous process that needs an update for conformity with modern trends in Arabic Literature. This article, therefore, explores divergent views of scholars on the meaning of "al-Naqd" in Arabic literary criticism. It traces the history of Arabic literary criticism from Pre- Islamic period to the modern time especially its trends in the Contemporary Period. It explains the distinction between a critique and a narrator. Ideal qualification of a critique and his characteristic features receives adequate attention. While sample of an ideal Arabic Literary Criticism on poetry and prose in the contemporary period serves a model of modern method for Arabic critics .